More Efficient VLR Group Signature Based on DTDH Assumption - Lizhen Ma (Institute of Advanced Engineering and Science, 2012)
In VLR (verifier-local revocation) group signature, only verifiers are involved in the revocation of a member, while signers are not. Thus the VLR group signature schemes are suitable for mobile environments. To meet the requirement of speediness, reducing computation costs and shortening signature length are two requirements at the current research of VLR group signatures. A new VLR group signature is proposed based on q-SDH assumption and DTDH assumption. Compared with the existing VLR group signatures based on DTDH assumption, the proposed scheme not only has the shortest signature size, but also has the lowest computation costs , and can be applicable to mobile environments such as IEEE 802.1x. DOI: http://dx.doi.org/10.11591/telkomnika.v10i6.1428